Pengukuran Kinerja Portofolio Investasi Dengan Menggunakan Indeks Sharpe Pada Emiten Sektor Transportasi Dan Logistik Yang Terdaftar Di Bursa Efek Indonesia Sebelum Dan Selama Masa Pandemic Covid - 19 - Mahaitin Hasohan Sinaga; Wico Jontarudi Tarigan; Marintan Saragih (Politeknik Ganesha Medan, 2022)
The term portfolio is often used to provide an understanding of a set of investments owned by investors in various types of investment instruments such as bonds, mutual funds, stocks, properties, and so on. To measure whether the portfolio carried out by investors has provided an optimal level of return, investors need to measure the performance of their placed investments. The Transportation & Logistics sector is expected to experience a negative impact due to the COVID-19 pandemic. The main problem in this study lies in measuring portfolio performance for companies that are included in the Transportation & Logistics Sector where portfolio performance before the Covid pandemic will be compared with portfolio performance during the Covid pandemic. The purpose of this study is to test and analyze whether the increase or decrease in the Transportation and Logistics Sector stock index is caused by differences in portfolio performance before and during the Covid pandemic. The research method used in this case is a quantitative descriptive method. Data analysis methods in this study include normality test followed by paired sample t-test (if normally distributed) and Wilcoxon test (if not normally distributed). The results showed that there were no significant differences regarding the performance of stock portfolios for companies listed in the Transportation and Logistics Sector during the COVID-19 pandemic when compared to the stock portfolio performance in the period before the COVID-19 pandemic.